Extraction of Polyphenols from Cydonia Oblonga Leaves and Their Effect on Mitochondrial Membrane Stability - Matmurotov Bakhtishod; Madrakhimova Sakhiba; Soliyev Nuriddin; Matchanov Alimjan (BIO Web of Conferences)
Cydonia oblonga Mill. (quince) is a fruit tree native to Azerbaijan, Dagestan, Turkmenistan, and Iran, known by various names including Baher Dana in Urdu and Behi in Hindi. Widely cultivated in Portugal, Turkey, Central Asia, India, and Europe, quince cultivars vary in flowering time and yield. High-yielding cultivars such as Aurora, Zoloto Skif, and Sophia show strong environmental adaptation. New cultivars such as Zolotistaya (28.4 mg/100 g vitamin C) and Padarok (32.3 mg/100 g) are rich in vitamin C and catechins. Phenolic compounds in quince leaves, particularly tannins (11%), have antidiarrheal properties. Extraction methods showed high phenolic content when the leaves were dried at optimal temperatures and extracted using ethanol systems. Quince polyphenols exhibit antioxidant and membrane stabilizing effects, which were observed in mitochondria under Fe2+/ascorbate stress, with inhibition values up to 90.3% at 30 μg/mL PF-4 extract. The study concludes that quince leaf extracts have significant antioxidant potential for pharmaceutical applications.